Community Structure of Macrozoobenthos in Lake Limboto - Abdul Hafidz Olii; Arfiani Rizki Paramata (The NIKe Journal, 2020)
This study aims to determine the structure of the macrozoobenthic community in Limboto Lake, Gorontalo Province. Sampling was carried out at 5 stations and 3 repetitions using the Ekman Grab tool and prepared with a filter with a net size of 100 µm. Collecting data using purposive random sampling method and the influence of the macrozoobenthic community structure with physical and chemical parameters was analyzed using the CANOCO 4.5 application. The results showed that the macrozoobenthic community structure in Limboto Lake varied, with the diversity index at Station 1 and Station 2 being in the medium category, Station 3, Station 4 and Station 5 being classified as low, the uniformity index at Station 1 and Station 2 was evenly distributed, Station 3, Station 4 and Station 5 are uneven. The dominance index at Station 3, Station 4 and Station 5 shows that there are species that dominate. The highest total macrozoobenthic abundance was at Station 3, namely 427,643 individuals / m3 and the lowest was at Station 2, namely 2,038 individuals / m3. The results of the analysis showed that the substrate had the greatest influence on the macrozoobenthic community structure and was followed by other physical-chemical parameters. Keywords: Macrozoobenthos; Lake Limboto; community structure